Proceedings of the EduARCHsia &Amp; Senvar 2019 International Conference (EduARCHsia 2019) 2020
DOI: 10.2991/aer.k.200214.031
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of precast foam concrete integrated with green roofs system

Abstract: The increase in urban temperature because of the urban heat island phenomenon affected energy usage for the building sector. Most of the energy usage in the building is for the air conditioning system to achieve thermal comfort. It is necessary to reduce the cooling load by minimizing heat gain to the building so that the air conditioning system uses less energy consumption. Passive design with a green roof system offers a solution to reduce heat gain from solar radiation through the roof. However, only a few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The high temperatures in Indonesia appear to be a major issue in Stage 1 for Indonesia. Jakarta, as the metropolitan city in Indonesia, has average daytime temperatures that could reach up to 35 • C. The surface of a roof exposed to the sun during the day can be affected by temperatures as high as 50 • C [51]. In order to limit the heat absorption into buildings, the development of GRs in Indonesia is important.…”
Section: Stages Of Green Roofs In Asean Countriesmentioning
confidence: 99%
See 4 more Smart Citations
“…The high temperatures in Indonesia appear to be a major issue in Stage 1 for Indonesia. Jakarta, as the metropolitan city in Indonesia, has average daytime temperatures that could reach up to 35 • C. The surface of a roof exposed to the sun during the day can be affected by temperatures as high as 50 • C [51]. In order to limit the heat absorption into buildings, the development of GRs in Indonesia is important.…”
Section: Stages Of Green Roofs In Asean Countriesmentioning
confidence: 99%
“…Several GR research studies and developments, which are categorized as Stage 3, are also being conducted. A study by Munir found that the use of lightweight foamed concrete and a green roof reduces construction loads and cooling loads for air conditioning systems [51]. Moreover, as an alternative to concrete, corrugated zinc roofing could be used as the base of a building's green roof.…”
Section: Stages Of Green Roofs In Asean Countriesmentioning
confidence: 99%
See 3 more Smart Citations